A fatal complication in a patient with heparin-induced thrombocytopenia type II re-exposed to heparin - Hoffmann, Ursula; Huhle, Günter; Rossol-Haseroth, Karin; Heene, Dieter L.; Harenberg, Job (European journal of orthopaedic surgery & traumatology, 1999)
The heparin-induced thrombocytopenia type II is a rare but important drug related complication associated with thrombocytopenia and thrombosis. We report on a patient with elective revision of the total hip arthroplasty. Preoperatively for nineteen days, the patient received unfractionated heparin 5000 IU three times daily for thromboprophylaxis. Postoperatively the patient developed a platelet drop from 236000/μl to 69000/μl an iliac vein thrombosis and pulmonary embolism. In assumption of heparin induced thrombocytopenia anticoagulation was switched to danaparoid-sodium subcutaneously. Platelet count rised to normal values while three days. Because of a negative heparin-induced platelet aggregation assay, anticoagulation was switched to a PTT controlled high dose intravenous unfractionated heparin. Two days after re-exposition to heparin platelet counts dropped to 34000/μl blood. The patient died 12 days after readministration of heparin due to respiratory and circulatory failure. Postmortem analysis of serum revealed positive heparin/platelet factor 4 IgG-antibodies.
Gesehen am 05.05.2022